Small interfering RNA molecules as potential anti-human rhinovirus agents: in vitro potency, specificity, and mechanism - Phipps, Krista M.; Martinez, Alejandro; Lu, Jin; Heinz, Beverly A.; Zhao, Genshi (Antiviral research, 2004)
RNA silencing or interference (RNAi) is a sequence-specific, post-transcriptional process of mRNA degradation. The degradation of target gene mRNA can be induced by short dsRNA molecules (21–25-nt) corresponding to the sequence of the target gene to be silenced. Short dsRNA molecules have been shown to be very effective in inducing RNA silencing in several human cell lines. In this study, we have shown that short dsRNA molecules corresponding to the human rhinovirus-16 (HRV-16) genome induce effective inhibition of the viral replication in cell culture. This inhibition is sequence-specific and dose-dependent. A single or double nucleotide sequence change in an effective dsRNA molecule can significantly reduce the ability of the molecule to induce RNA silencing. Reducing the length of siRNA molecules to 19-nt or shorter abolishes their activity. Therefore, the results of this study demonstrate certain siRNA molecules are inhibitory for the replication of HRV-16 when transfected into human cells; further studies are warranted to explore the potential clinical value of these siRNA molecules as anti-human rhinovirus agents.